2015
DOI: 10.1002/jtr.2050
|View full text |Cite|
|
Sign up to set email alerts
|

Profiling the Heritage Experience in Macao's Historic Center

Abstract: This paper applies Pine and Gilmore's four realms of experience – Esthetic, Escapism, Entertainment and Education – to investigate Macao's Historic Center in terms of the experience value attached to different heritage sites by tourists, with implications for understanding the experience profile of heritage tourism sites in general. The research is based on a survey of 700 tourists. Dominant experience profiles for the sites, which differ from that of the Historic Center as a whole, are identified and discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…We report the detailed findings of the comparisons of the sites in terms of their experience values elsewhere (Suntikul & Jachna, 2015). One such finding that has a bearing on this paper is that, of the four experience values, the sites of Macao's Historic Center were rated most highly in terms of the esthetic dimension, and lowest in terms of entertainment.…”
Section: Methodsmentioning
confidence: 96%
“…We report the detailed findings of the comparisons of the sites in terms of their experience values elsewhere (Suntikul & Jachna, 2015). One such finding that has a bearing on this paper is that, of the four experience values, the sites of Macao's Historic Center were rated most highly in terms of the esthetic dimension, and lowest in terms of entertainment.…”
Section: Methodsmentioning
confidence: 96%
“…2-Esthetic Experience in Tourism and Hospitality. Heritage and historical sites among the (4Es) factor( dimension ) of experiences, can be regarded as more esthetic-based experience in nature ,as the (Suntikul and Jachna, 2015) finding from the research study which based on seven hundred international tourists in Macao's historic center concluded that twenty five sites among thirty one possess the ranking of entertainment, esthetic, and escapism and educational experiences profile of perception of the experience value of the historic core center. It has showed that esthetic -based experience is dominant than other experience in heritage and historical sites.…”
Section: Memorable Tourism Experience (Mte) and The Four Tourists Sermentioning
confidence: 96%
“…The 4E model was tested in the field of tourism for the first time by Oh and others (2007), who had not found an earlier valid measurement scale regarding the model. Since then, measurement methods based on the 4E model were used several times in the different fields of tourism (Oh, Fiore & Jeoung, 2007;Jurowski, 2009;Mehmetoglu & Engen, 2011;Willard, Frost & Lade, 2012;Radder & Han, 2015;Suntikul & Jachna, 2016;Ásványi, Mitev & Jászberényi, 2018).…”
Section: Esthetic Experiencementioning
confidence: 99%